21ST CENTURY TEACHER’S TRANSVERSAL COMPETENCIES: THEORETICAL ANALYSIS - Tkachenko, Nataliia; Kovalchuk, Vasyl; Wenjing, Yuan (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2023)
In the current situation, a significant part of the existing models of training specialists in the field of education no longer meet the conditions of the labour market. The most important pedagogical skills in the present time are significantly different from the skills that were relevant until recently. Knowledge is still important, but modern teachers also need to have transversal competencies to succeed in their professional activities. So, the research aim is to study the content of the phenomenon “transversal competences”, which will make the process of their forming more effective. To achieve the aim the scientific literature and pedagogical practice was analysed. It was found out that transversal competences are transferable and reusable skills that can be applied in a wide variety of situations and work settings. Transversal competencies are considered as 21st century skills and correlate mostly with human ability to solve problems, related to technological advances and intercultural communication.The analysis of the sources revealed the inconsistency in the use of terms denoting the studied concept and considerable diversity in defining the content of transversal competencies, as different sources distinguish different sets of skills. Based on the framework of transversal competences worked out by UNESCO the modern teacher’s transversal competencies were characterized in six domains: 1) critical and innovative thinking, 2) interpersonal skills, 3) intrapersonal skills, 4) global citizenship, 5) media and information literacy, and 6) others.